Insulin Resistance and Non-Alcoholic Fatty Liver Disease in Premenopausal Women with Metabolic Syndrome - El-Sehrawy, Amr Ali; State, Omnia; Elzehery, Rasha Rizk; Mohamed, Ahmed Salem (Hormone and Metabolic Research, 2021)
It is suggested that estrogen protects premenopausal women against non-alcoholic fatty liver disease. From another perspective, the relation between metabolic syndrome (MetS) and non-alcoholic fatty liver disease (NAFLD) is bidirectional. Role of insulin resistance (IR) in NAFLD continues to be a matter of debate. The present study aimed to assess the relation between IR and NAFLD in premenopausal women with MetS. The study included 51 premenopausal women with MetS. In addition, there were 40 age-matched healthy controls. All participants were subjected to careful history taking and thorough clinical examination. Performed laboratory investigations included fasting blood glucose, fasting insulin, lipid profile, and liver functions. Calculation of IR was achieved by the Homeostasis Model Assessment (HOMA-IR). NAFLD was graded into three grades according to findings of abdominal ultrasound. Patients had significantly higher BMI, SBP, DBP, FBG, fasting insulin, HOMA-IR, total cholesterol, triglycerides, and LDL levels when compared with controls. They also had significantly lower HDL levels in comparison to controls. Moreover, they have more advanced grades of NAFLD in contrast to controls. Comparison between patients with various grades of NAFLD regarding the clinical data revealed significant increase of fasting insulin and HOMA-IR levels with advancing NAFLD grade. Using multivariate regression analysis, HOMA-IR was an independent predictor of advanced NAFLD grade. In conclusion, the present study documented a combined inter-relation between MetS, IR, and NAFLD in premenopausal women with MetS. IR is correlated with NAFLD grade.
Keywords: metabolic syndrome; non-alcoholic fatty liver disease; insulin resistance